2014
DOI: 10.1111/are.12388
|View full text |Cite
|
Sign up to set email alerts
|

Effect of various sources of dietary additive on growth, body composition and serum chemistry of juvenile olive flounder (Paralichthys olivaceus)

Abstract: Asia traditional herbal feed additives have often been shown to have beneficial effects on disease resistance, growth, feed conversion and protein conversion. There have been few studies on the use of these feed additives in olive flounder diets. The present study was designed to determine if there are benefits associated with the inclusion of any of these traditional herbal feed additives in olive flounder diets. One thousand two hundred sixty juvenile fish averaging 6.5 g were randomly distributed into 36, 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 32 publications
1
7
0
Order By: Relevance
“…Most of the herbs and spices could stimulate the function of pancreatic enzymes, some also increase the activity of digestive enzymes of gastric mucosa, and enhance gastrointestinal digestion and absorption capacity [9]. Thus, our results were consistent with the previous literature reports [20,[32][33][34].…”
Section: Discussionsupporting
confidence: 93%
“…Most of the herbs and spices could stimulate the function of pancreatic enzymes, some also increase the activity of digestive enzymes of gastric mucosa, and enhance gastrointestinal digestion and absorption capacity [9]. Thus, our results were consistent with the previous literature reports [20,[32][33][34].…”
Section: Discussionsupporting
confidence: 93%
“…Cho (2011) conducted an experiment with Paralichthys olivaceus, fed with a basal diet containing 1 g/100g fig and onion extract meal for 6 weeks, and he found that the use of 1 g/100g onion extract meal improved the fish performance (weight gain and specific growth rate). In another study, it was determined that there is no change in the survival rate, weight increase and specific growth rate of Paralichthys olivaceus (6.5 g) that was fed with a diet containing %2,5 fig (Ficus carica) (Lee et al, 2015 ) It was generally observed through the nutritional value and growth performance analyses that fig and onion addition to the feed with the rate of 1,3 g/100g had positive results. These differences could be explained by the different application time of feeding and fish species, or the level of fig and onion extract in the diets.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have reported that oral administration of fig and onion extract in Paralichthys olivaceus (Cho, 2011), fig in Paralichthys olivaceus (Lee et al, 2015) improved growth performance.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Cho (2011) stated that fig extract did not show positive effect on growth in rainbow trout. Lee et al (2015) also reported no change in the survival rate, weight increase and specific growth rate of Paralichthys olivaceus (6.5 g) that was fed with a diet containing % 2,5 fig (Ficus carica).…”
Section: Discussionmentioning
confidence: 97%
“…In the limited number of researches carried out with the aim of determining the opportunity of using plants and the active agents they contain in the cultivation, it has been reported that plant extracts added to the feed and water enhance the feed consumption, feed conversion, and growth and carcass quality (Simsek et al, 2005;Immanuel et al, 2009;Oskoii et al, 2012). Several studies have reported that oral administration of fig extract in Paralichthys olivaceus (Cho, 2011), and Paralichthys olivaceus (Lee et al, 2015) and rosemary extract in African catfish (Turan and Yiğitaslan, 2016) improved growth performance.…”
Section: Introductionmentioning
confidence: 99%